(3GdeTcGI aj eSGFd GdNeS hGdRcGIs - (3GdgeOGfj, GdcGXej, EeGe GdMQejf, eMeO Hf YHO GdhgGH Hf OGhO, J (B1305(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3CMSf eG(B... (3GdeQA HjOg hjcfRg aj jheg dZOg(B... (3CeG HYO(B... (3gPg ahGFO aj eSGFd GdNeS(B...s
(3BNQgG (B:s
(3dchf Jchjfg ajg ZjQ eYghO hEdG ageG aj GdMce ShGA hGddg GdYGde(B. (3gPG BNQ GdLRA GdChd ef cJGH GdNeS ef cJGH GdeTcGIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B472s
(3GdPQjYI, Qbe(B: 3914s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B472s
(3GdPQjYI, Qbe(B: 3914s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis